IMPLIKASI DISARTRIA FONEM /r/ TRILL (KECADELAN) TERHADAP PELAFALAN FONEM /t/ DAN /d/ - Dewa Ayu Dyah Pertiwi Putri; I Ketut Subagia; I Made Astu Mahayana; Ni Nyoman Muryatini; Kuntayuni (Universitas Warmadewa, 2023)
This research is intended as a pilot study to find out the implications of the dysarthria of the phoneme /r/ trill on the quality of other consonant phonemes produced at the same place of articulation. This study was designed using a descriptive quantitative-qualitative approach with field methods. In collecting data, the observation method was used to collect data in the form of consonant and vowel phonemes produced by 4 dysarthria samples and 4 non- dysarthria samples. The collected data were then analyzed using extralingual and intralingual comparison methods. The results of the study show that if the place of articulation where a sound is produced has a problem, then the problem will affect all the sounds produced in that place. The hard production of the alveolar trill /r/ phoneme in dysarthria sufferers has implications for the production of other alveolar sounds, namely /t/ and /d/ which become weaker and more nasal. Keywords: dysarthria; acoustic features; /r/ trill phoneme